Solving mould and condensation problems: A Dehumidifier Trial in a Suburban House in Britain - Ray Galvin (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2010)
High humidity can lead to condensation and mould formation if a house is well sealed and indoor temperatures fall significantly during the night. Solutions that have been offered are to keep heaters on throughout the night, to increase the thickness of insulation, or to install heat-exchange ventilators. These solutions are expensive. The cultural practice of heating homes to around 20°C during the day and evening has been challenged, but lack of heating will not prevent natural temperature swings. A more direct solution is to remove the moisture from the air using a dehumidifier. This study reports a controlled 28-night trial of a dehumidifier in a suburban UK home in winter. The machine drew an average of 680 ml of water out of the air each night and consumed around 1 kilowatt of electrical energy per night, with a high correlation between volume of water collected and energy consumed. Occupants reported that the previously severe condensation problem was solved, and measurements showed that the latent heat of the collected moisture also increased the ambient temperature. The estimated cost of running the machine for half the nights of the year is 23, an order of magnitude cheaper than other solutions.
Keywords: 330; Dehumidifier; condensation; mould; fuel poverty; insulation; Gebäudemanagement; Energietechnik; Energiesparen; Großbritannien